Single-cell RNA sequencing and spatial transcriptomic analysis reveal a distinct population of G6PD+ cells with aberrant bile acid metabolism in hepatocellular carcinoma - Jiang, Xing; Quan, Haiyan; Yin, Ting; Yao, Hailun; Li, Yajun; Peng, Bin; Yuan, Xinye; Zeng, Weiguang; Chen, Honghui; Li, Rong (Frontiers in Immunology, 2026)
BackgroundMetabolic reprogramming is a hallmark of hepatocellular carcinoma (HCC). Among various metabolic pathways, bile acids act not only as crucial metabolites but also as key signaling molecules that regulate diverse physiological and pathological processes in the liver. However, the biological functions and clinical implications of bile acid metabolism in HCC progression remain largely unclear.MethodsSingle-cell transcriptomic data from 67 patients with HCC were integrated to construct a bile acid metabolism scoring system. Pseudotime trajectory analysis was employed to characterize the differentiation patterns of cells exhibiting abnormal bile acid metabolism. Spatial transcriptomics was used to explore their spatial distribution features. Furthermore, machine learning algorithms were applied to analyze transcriptomic data from HCC cohorts to develop a prognostic prediction model. The findings were complemented by immune infiltration analysis, molecular characterization, and drug sensitivity prediction using CellMiner, followed by molecular docking validation.ResultsG6PD+ malignant tumor cells with high bile acid metabolism scores exhibited enhanced bile acid metabolic activity, accompanied by activation of macrophages and endothelial cells. These cells were predominantly localized at the tumor boundary region. A prognostic prediction model based on G6PD+ expression successfully identified a high-risk subgroup with significantly poorer outcomes. In vitro experiments demonstrated that knockdown or overexpression of G6PD markedly affected the proliferative, migratory, and invasive capacities of HCC cells.ConclusionThis study reveals that bile acid metabolism promotes HCC progression by facilitating vascular network formation and establishing an immunosuppressive tumor microenvironment. The bile acid metabolism scoring system may serve as a novel prognostic biomarker and provide a theoretical foundation for developing precision therapeutic strategies in HCC.